The Down-Regulation of MicroRNA-497 Contributes to Cell Growth and Cisplatin Resistance Through PI3K/Akt Pathway in Osteosarcoma - Shao, Xue-jun; Miao, Mei-hua; Xue, Jun; Xue, Jian; Ji, Xue-qiang; Zhu, Hong (Cellular physiology and biochemistry, 2015)
Background: Down-expression of microRNA-497 (miR-497) was often found in malignancies. The purposes of this study were to determine the expression of miR-497 in human osteosarcoma and to establish the association between miR-497 expression with cell survival and the sensitivity to cisplatin in human osteosarcoma cells. Methods: The effects of ectopic miR-497 expression on the cell survival and cisplatin sensitivity in osteosarcoma cells were measured by the Cell Counting Kit-8 (CCK-8) assay. Quantitative real-time PCR (qRT-PCR) was utilized to determine the expression of miR-497. The effects of ectopic miR-497 expression on the expression of VEGFA, Akt and p-Akt were determined by western blot. Results: Real-time quantitative PCR analysis revealed that miR-497 was significantly down-regulated in osteosarcoma tissues and in the osteosarcoma cell line SAOS-2 compared with adjacent nontumorous osteosarcoma tissues and normal human osteoblasts. Up-regulation of miR-497 inhibited cell survival and enhanced the sensitivity to cisplatin in osteosarcoma cells. In addition, knockdown of miR-497 induced osteosarcoma cells growth and cisplatin resistance. Luciferase reporter assay and western blot confirmed that VEGFA was a direct target of miR-497. PI3K inhibitor LY294002 abrogated miR-497 inhibitors induced cisplatin resistance. Conclusion: Taken together, our results suggest that miR-497 modulates the sensitivity to cisplatin at least in part through PI3K/Akt pathway in osteosarcoma cells.